(untitled) (Agricultural Engineering, 2017)
Technology of processing of agricultural raw material and production residues from agri-food industry often requires their dewatering. Digestate is one of such materials i.e. the mass remaining after the bio-gasification process, which has great hydration (above 85%). The objective of the research was to know the impact of dewatering on the change of water content in digestate from biogas in Piekoszów. A mechanical dewatering process was carried out and reflected the conditions of operation of screw presses for dewatering of plant raw materials, whose screen internal diameter is 160 mm. Knowing the impact of pressure on the dynamics of raw material moisture decrease will allow modelling of the operation of industrial devices with similar operation parameters. Thus, a research on the dewatering process with the use of pressure within 0.58-2.91 MPa and slotted screens with meshes size of 0.1; 0.2 and 0.3 mm were carried out. The analysis of the obtained results indicates that an effective process of dewatering of the investigated digestate takes place at the working pressure to 1.74 MPa regardless the applied screen. Further increase of pressure does not cause a significant decrease of moisture in the investigated material.